Characteristics of Patients with Abnormal Scars Managed at a Tertiary Hospital in Indonesia: A Descriptive Study - Shafira Irmalia; David Sontani Perdanakusuma; Dwi Murtiastutik (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2026)
Highlights: Burn scars were the leading cause of abnormal scars. Surgery was the primary treatment for abnormal scars.   Abstract Introduction: Human skin is prone to damage, resulting in abnormal scarring that can adversely affect individuals and society. This study aimed to examine the frequency, characteristics, and treatment options of patients with abnormal scars treated at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from 2019 to 2023. Methods: This was a descriptive retrospective study that utilized 48 medical records of patients with abnormal scars at the Department of Plastic Reconstructive and Aesthetic Surgery, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from 2019 to 2023. Data analysis was performed using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) for Windows version 25.0. The variables in this study included demographic characteristics, etiology of the scar, region, size, and management of abnormal scars. Results: Of 48 patients, the highest incidence was in 2023 (29.2%). The majority of patients were female (60.4%) and aged 15-49 years old (41.7%). Burns were the primary etiology of scars (35.4%), and most scars measured over 20 cm² (34.5%). Surgical treatment was the most common management option (54.7%). Conclusion: Patients with abnormal scars are most frequently affected by burn scars. A significant proportion of these individuals present with extensive hypertrophic keloid scars, for which surgical intervention is the most often used therapeutic method.